AGRO-INDUSTRIAL INTEGRATION AS A FACTOR IN THE DEVELOPMENT OF ENTERPRISES FOR THE PRODUCTION AND PROCESSING OF OIL CROPS PRODUCTS - LYTOVCHENKO, Liudmila (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The importance of the transition of economic and industrial relations to a higher level of development actualizes theoretical and practical research on agribusiness management based on modeling economic behavior in integration structures, considering modern global challenges. The study aims to determine the features, advantages, and disadvantages of agro-industrial integration as a factor in developing enterprises for producing and processing oilseed products in modern conditions. According to the results of the conducted research, it can be concluded that today, the enterprises for the production and processing of oil crop products need to strengthen their competitive positions in the target markets and, therefore, find ways to form and protect competitive advantages, both based on quality and costs. A clear, balanced strategy of agro-industrial integration can help in this. As practice shows, this is preceded by an analysis of the current model of economic behavior and the determination of changes in it due to new economic conditions. The features and types of such integration are clarified. An analysis of the advantages and disadvantages of vertical and horizontal integration was carried out. It is proven that the economic behavior of the enterprise as part of an integrated structure will differ depending on the state of the economy in the country where the business is based, as well as on the potential of partners, which will cause the achievement of a negative or positive synergistic effect. Integrative transformations are strategic decisions that require improving skills and business capabilities. The importance of the human factor in agro-industrial integration has been proven. This is because supply, production, logistics, and trade are different areas in the oil business and, therefore, are critical success factors. It was also found that positive changes in the external environment can cause changes in the internal environment and enterprises’ economic behavior. The problems accumulated during martial law, the closure (or loss) of business, and the chaotic economic behavior of many farmers today indicate that it becomes easier and unfounded with a thorough understanding of the motives of the enterprises’ behavior.